The ‘Butterfly Effect’ in Kim Stanley Robinson’s The Years of Rice and Salt - Nader Mostafa Helmy (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2025)
The ‘butterfly effect’ is an underlying principle of chaos theory— a branch of mathematics and physics developed by Edward Norton Lorenz in 1960s— resting on the notion that a small occurrence can influence a complex system. In the same vein, the butterfly effect as an interdisciplinary approach applied to sociohistorical studies describes how seemingly insignificant individual actions can initiate significant sociohistorical consequences within complex systems. Accordingly, the “butterfly effect” highlights the agency of individuals and the profound effects their choices can generate. Guided by this principle, the present study aims at exploring the alternate history presented in Kim Stanley Robinson's The Years of Rice and Salt (2002). The novel explores a pivotal point of divergence: what if the Black Death plague had annihilated 99% of Europe's population instead of a third. The Years of Rice and Salt also tries to speculate how the absence of European colonization and imperialism shapes the world, including the rise of new powers and the impact on cultural, political, and scientific advancements. Through the lens of the principle of the “butterfly effect”, the study attempts to offer a comprehensive understanding of the intricate interplay between sociopolitical conflicts and individual agency within the novel's micro-macro structure and to explore diverse perspectives on how these forces interact, shaping the course of history in this alternate reality."تأثير الفراشة" هو المبدأ الأساسي لنظرية الفوضى - وهو فرع من فروع الرياضيات والفيزياء أسسها عالم الرياضيات إدوارد نورتون لورينز في ستينات القرن الماضي. ويؤكد مبدأ ”تأثير الفراشة“ على أن الأعمال الفردية والتي تبدو غير ذات شأن قد تؤدي إلى نتائج تاريخية عظيمة داخل الأنظمة العلمية والسياسية والاجتماعية المعقدة. وبناء على ذلك، فإن مبدأ ”تأثير الفراشة“ يسلط الضوء على الدور المؤثر للافراد والنتائج المترتبة على خياراتهم. وعلاوة على ذلك، فإن مبدأ تأثير الفراشة يشير إلى أن الأحداث الطفيفة ظاهرياً يمكن أن تكون لها آثار كبيرة على الأحداث التاريخية.  واسترشاداً بمبدأ "تأثير الفراشة“، تهدف هذه الدراسة إلى استكشاف التاريخ البديل في رواية "سنوات الأرز والملح" (2002) للكاتب الأمريكي كيم ستانلي روبنسون. تسلط الرواية الضوء على نقطة محورية في التاريخ: ماذا لو كان وباء الموت الأسود قد أباد 99% من سكان أوروبا بدلاً من ثلث السكان؟ كما توضح الرواية تأثير غياب الاستعمار الأوروبي والإمبريالية الأوروبية على تاريخ العالم بداية من القرن الخامس عشر حتى القرن الحادي والعشرين، بما في ذلك ظهور قوى جديدة وتأثير ذلك على التطور الثقافي والسياسي والعلمي في مناطق مختلفة بالعالم. وتسعى الدراسة، من خلال تطبيق مبدأ "تأثير الفراشة"، إلى تقديم دراسة شاملة توضح التفاعل المعقد للصراعات الاجتماعية، السياسية، والوكالات الفردية وذلك في إطار هيكل الرواية الدقيق والكلي، علاوة على استعراض وجهات نظر متنوعة بشأن كيفية التفاعل بين هذه القوى، وتشكيل مسار التاريخ من خلال هذا الواقع البديل.